2011
DOI: 10.1002/glia.21225
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 signaling regulates remyelination by endogenous oligodendrocyte progenitor cells in a viral model of demyelination

Abstract: Following intracranial infection with the neurotropic JHM strain of mouse hepatitis virus (JHMV), susceptible mice will develop widespread myelin destruction that results in pathological and clinical outcomes similar to those seen in humans with the demyelinating disease Multiple Sclerosis (MS). Partial remyelination and clinical recovery occurs during the chronic phase following control of viral replication yet the signaling mechanisms regulating these events remain enigmatic. Here we report the kinetics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…Previous studies have demonstrated neuroprotective effects of CXCL12/CXCR4 in regulating the antiapoptotic kinase Akt (60) and various cell cycle proteins, whose aberrant expression in postmitotic neurons leads to cell death (2-4). This signaling pair also decreases excitotoxicity by regulating the subunit composition of extrasynaptic NMDA receptors (5) and promotes tissue repair by regulating differentiation and migration of progenitor cells in models of multiple sclerosis (7,61) and ischemia (8,62). Additionally, CXCL12 has been shown to block a reduction in hippocampal dendritic spines caused by the neurotoxin amyloid β (63), although this study did not report any changes in spine density in the absence of amyloid β.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated neuroprotective effects of CXCL12/CXCR4 in regulating the antiapoptotic kinase Akt (60) and various cell cycle proteins, whose aberrant expression in postmitotic neurons leads to cell death (2-4). This signaling pair also decreases excitotoxicity by regulating the subunit composition of extrasynaptic NMDA receptors (5) and promotes tissue repair by regulating differentiation and migration of progenitor cells in models of multiple sclerosis (7,61) and ischemia (8,62). Additionally, CXCL12 has been shown to block a reduction in hippocampal dendritic spines caused by the neurotoxin amyloid β (63), although this study did not report any changes in spine density in the absence of amyloid β.…”
Section: Discussionmentioning
confidence: 97%
“…In a viral model of demyelination, CXCR4 signaling was indispensable for OPC proliferation and enhanced remyelination (Carbajal et al, 2011). Furthermore, AMD3100 treatment Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of the CXCR4/SDF-1α signaling pathway on NPCs and MSCs increases their migratory capacity, survival, and remyelinating capacity, both in vitro on slice cultures (Corti et al, 2005;Imitola et al, 2004b), as well as in vivo upon focal transplantation into rodents with experimental cerebral ischemia (Robin et al, 2006;Wang et al, 2008), and JHMV-induced demyelination (Carbajal et al, 2010(Carbajal et al, , 2011. In human NPCs, integrins α2, α6, and β preferentially mediate the homing toward the vasculature, whereas the CXCR4/ SDF-1α signaling pathway regulates homing through the brain parenchyma (Carbajal et al, 2010;Mueller et al, 2006;van der Meulen et al, 2009).…”
Section: Homing and Extravasationmentioning
confidence: 99%